Samples: from the patient to the laboratory the impact of preanalytical variables on the quality of laboratory results (Wiley-VCH, 2003)
CD-ROM contains WHO regulations and recommendations. Compilation of findings from the literature and those obtained in practice on the use of anti coagulants and provides a list of analytes containing the available data on reference intervals, biological hal-life times, stability and influence and interference factors.